Forensic Analysis of 25 Cases of Diffuse Brain Atrophy after Trauma - WANG Yao-bin, WANG Li-li, ZHONG Shi-liang (Fayixue Zazhi, 2019)
Objective To study the forensic features of diffuse brain atrophy after trauma, the relationship between age and interval time of post-traumatic brain atrophy, and the relationship between the degree of craniocerebral injury and that of brain atrophy. Methods The forensic features of 25 cases of diffuse brain atrophy after craniocerebral trauma were retrospectively analyzed from aspects of gender, age, craniocerebral injury characteristics, and imaging characteristics of brain atrophy. Pearson correlation analysis was used for statistical analysis. Results Diffuse brain atrophy after trauma could occur in any age group, dominated by severe brain injury. The Pearson correlation coefficients （r） between the time interval of brain atrophy and age were 0.442 （P<0.05）, 0.341 （P>0.05）, and 0.904 （P<0.05） for the overall cases, the group over age 50, and the group under age 50, respectively. The correlation coefficient between the degree of brain injury and that of brain atrophy was 0.579 （P<0.05）, and that between severe brain injury and brain atrophy was 0.788 （P<0.05）. Conclusion The more serious the brain injury, the more severe the brain atrophy. Various degrees of diffuse brain atrophy can occur in severe craniocerebral injury, and diffuse brain atrophy is usually mild and moderate after mild and moderate craniocerebral injury. In the practice of forensic clinical identification, a comprehensive analysis should be conducted with the combination of case materials when the identified person has high risk factors leading to brain atrophy （e.g., hypertension, diabetes, etc.）, plus injury and illness relationship analysis if necessary.